Pendidikan Ilmu Pengetahuan Sosial Dalam Mengatasi Krisis Identitas Akibat Penggunaan Media Sosial - Taufiq Hidayat; Suryadi Fajri (FKIP, Universitas Palangka Raya, 2024)
This research is motivated by the influence of social media on identity crises. Students at the junior high school level are active social media users. Because social media has become a center for information. An identity crisis arises in students if they become a minority on social media. The influence of social media on students includes aspects of how to think, adapt and behave socially. The aim of this research is to develop ideal and confident student character. This research is the result of research based on a literature review (library research). Because the research method used is a qualitative method which is presented descriptively and analytically. The results of this research are to provide understanding to social studies teachers in efforts to overcome identity crises in students. Basically, social studies education has an influence on increasing students' self-confidence, namely; foster feelings of respect in one's environment and accept one's own situation without comparing it with others.